2008
DOI: 10.1002/ajp.20543
|View full text |Cite
|
Sign up to set email alerts
|

Ranging patterns and habitat use of Sulawesi Tonkean macaques (Macaca tonkeana) in a human‐modified habitat

Abstract: The goal of this study was to investigate the ecological flexibility of Tonkean macaques (Macaca tonkeana) by examining how they respond to human-induced habitat alteration. To do so, I observed movement patterns, forest strata use, microhabitat use, and home range use in two groups that occupied habitats with different levels of human alteration and habitat quality in Lore Lindu National Park, Sulawesi, Indonesia. The group occupying the heavily altered habitat (Anca) spent a significantly greater proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 44 publications
4
48
2
Order By: Relevance
“…Similarly, Melfi and Feistner (2002) found through direct comparison that there were greater differences between two captive groups and between two wild groups of crested black macaques Macaca nigra than for comparisons between captive and wild groups. In support of other studies on wild Tonkean macaques (Riley, 2007(Riley, , 2008, we suggest that resting is the most prominent activity both in the wild and captivity, whilst foraging is not. The most striking differences between wild and captive groups are in socializing and moving activities.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, Melfi and Feistner (2002) found through direct comparison that there were greater differences between two captive groups and between two wild groups of crested black macaques Macaca nigra than for comparisons between captive and wild groups. In support of other studies on wild Tonkean macaques (Riley, 2007(Riley, , 2008, we suggest that resting is the most prominent activity both in the wild and captivity, whilst foraging is not. The most striking differences between wild and captive groups are in socializing and moving activities.…”
Section: Discussionsupporting
confidence: 90%
“…Previous reports stated that Tonkean macaques spent most of their time in trees (Pombo et al, 2004;Riley, 2007Riley, , 2008. We showed that animals tended to spend more time in trees during the leafing season (spring) and were therefore sensitive to seasonal changes.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Consequently, these macaques travel much less widely in search of food. Concurrently, group size would be a main factor affecting ranging behavior in primates, with large-sized groups typically with larger home ranges and longer daily path lengths [36][37][38]. At only 32-46 individuals [39], the studied group is smaller than those observed in other Macaca species: M fascicularis (66 individuals, Jamieson, 1998), M fuscata (41 individuals) [28], M nemestrina (49-81 individuals) [31], or M nigra (42-97 individuals) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, group size would be a main factor affecting ranging behavior in primates, with large-sized groups typically with larger home ranges and longer daily path lengths. [36][37][38] At only 32-46 individuals, 39 the studied group is smaller than those observed in other Macaca species: M fascicularis (66 individuals, Jamieson, 1998), M fuscata (41 individuals), 28 M nemestrina (49-81 individuals), 31 or M nigra (42-97 individuals). 33 Barbary macaques in the upper Ourika valley used large parts of their home range very infrequently, concentrating their activities around and within crops.…”
Section: Discussionmentioning
confidence: 99%